REVITALISASI TEMPAT WUDHU BANGUNAN SEKOLAH DASAR ISLAM TERPADU AN NURILLAH, DI DESA KARANG ANYAR KECAMATAN BERINGIN KABUPATEN DELI SERDANG SUMATERA UTARA - Suita, Diana; Fitriana, Liza; Dafitri, Haida; Chiuloto, Kalvin; Simanjuntak, Johan Oberlyn; Simorangkir, Simon Petrus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The community service program in this Real Work Lecture program aims to revitalize the ablution area at An Nurillah Integrated Islamic Elementary School located in Karang Anyar Village, Beringin District, Deli Serdang Regency, North Sumatra. The previous condition of the ablution area was unsuitable for use due to clogged drains, inadequate floors, and damaged sanitation facilities, which hampered the smooth ablution activities of students and teachers before worship. The implementation of this community service activity went through several stages starting from an initial condition survey, redesign planning, material procurement, and renovation. The renovation included the installation of 10 water taps at the front and back, the installation of ceramics on the walls and floors, painting, and the finishing process so that the ablution area is clean, safe, and comfortable to use. This revitalization is very important to support the implementation of worship for students and all school residents at An Nurillah Integrated Islamic Elementary School, in Karang Anyar Village, Beringin District, Deli Serdang Regency, North Sumatra, which makes morals and Islamic teachings the main foundation of education. In addition to improving physical facilities, this program also provides an educational impact to students regarding the importance of maintaining and preserving public facilities to ensure their continued cleanliness.The success of this community service program is a concrete example of the synergy between students as implementers of the community service program and the school community in creating an environment that supports spiritual activities and school cleanliness. With the presence of a revitalized ablution area, it is hoped that a more conducive school environment will be created to support worship discipline and increase awareness of environmental cleanliness. The sustainability of this program can be continuously encouraged with the active participation of the school community in maintaining the facility for long-term use. This program can also be used as a model for managingNurillah Integrated Islamic Elementary School, in Karang Anyar Village, Beringin District, Deli Serdang Regency, North Sumatra, and provided real experience for students in implementing community service in a professional and structured manner